Influence of cracking and rough surface properties on the transfer of forces in cracked concrete. (15th December 2020) - Tirassa, Max; Fernández Ruiz, Miguel; Muttoni, Aurelio
Highlights: A comprehensive review of the phenomenon of aggregate interlock is presented. New experimental data is provided, allowing for detailed kinematical control. A mechanical model considering surface roughness and crack kinematics is presented. Modelling accounts for the contribution of residual tensile strength to the response. Abstract: Aggregate interlocking is acknowledged as one of the most significant actions transferring shear forces in cracked concrete structures and has been investigated for several decades. Despite the many experimental programmes and previous efforts to develop models based on mechanical approaches, a number of instrumental issues of the phenomenon are still not fully understood. For example, most researches have focused on the capacity to transfer forces through a given crack surface. However, the development of secondary cracks developing from the initial crack due to stress concentrations has traditionally been disregarded, despite the fact that these secondary cracks are governing in many cases for the overall strength. Also, other important aspects have not been comprehensively investigated, such as the contribution of the residual strength of concrete both in tension and shear during crack development. In this paper, the results of an experimental programme aimed at the fundamental understanding of the transfer of forces in cracked concrete is presented. This programme comprises detailed measurements of the surface roughness after failure. On that basis, a model considering both the crack surface properties and those of the concrete material is presented, accounting also for the potential development of secondary cracking. The model estimates the transferred forces by considering surface patches in contact and the contribution of the residual strength of the fracture process zone. The results of the model are compared to the test results showing consistent agreement both in terms of failure mode and the capacity to transfer forces as a function of crack opening and sliding.